The Influence of Board of Directors’ Characteristics on Corporate Social Responsibility Disclosure: Evidence from the Indonesian Energy Sector, 2021-2023 - Anshori Agung Nugroho; Banu Witono Witono (International Journal of Multidisciplinary Sciences and Arts, 2025)
This study examines the influence of board of directors’ characteristics—specifically gender diversity, board size, educational background, the presence of foreign directors, and board tenure—on the extent of Corporate Social Responsibility (CSR) disclosure. The research focuses on a critical and high-impact context: the Indonesian energy sector from 2021 to 2023. Employing a quantitative methodology with purposive sampling, the study analyzes a panel dataset of 54 firm-year observations from energy companies listed on the Indonesia Stock Exchange (IDX). CSR disclosure is measured using a comprehensive index based on the Global Reporting Initiative (GRI) Standards, and the hypotheses are tested using multiple linear regression analysis. The results reveal that board size has a statistically significant and positive influence on the level of CSR disclosure. Conversely, board gender diversity, the educational background of directors, the proportion of foreign directors, and board tenure do not demonstrate a significant effect. The model's Adjusted R2 of 0.214 indicates that 21.4% of the variation in CSR disclosure can be explained by the board characteristics examined. The findings suggest that in the highly regulated Indonesian energy sector, a larger board, which provides a broader pool of expertise and enhances monitoring capacity, is a key internal governance mechanism driving greater CSR transparency. These results offer valuable insights for corporate policymakers aiming to strengthen governance for sustainability and for regulators seeking to improve the quality of corporate reporting beyond mandatory compliance.